TINJAUAN FIQH MUAMALAH TERHADAP JUAL BELI BARANG CURIAN - Samiah Nainggolan (Adpertens: Jurnal Ekonomi dan Manajemen, 2024)
This paper discusses the legal status of stolen goods, both stolen goods that are not known to the buyer or stolen goods that are completely known to the buyer but he is still unsure whether the goods are stolen or not. To answer this problem the author uses a quantitative method with a literature or library approach, where the author looks for answers from various fiqh jinayah books. The findings in this article are that the practice of buying and selling stolen goods is strictly prohibited in Islam, especially buying goods whose status is clearly known to be the product of theft or is not clearly known, but there are indications that point to stolen goods, it is unlawful to buy them even if they are priced relatively cheap price.